Reprogramming barriers and enhancers: strategies to enhance the efficiency and kinetics of induced pluripotency. Issue 1 (December 2015) - Ebrahimi, Behnam
Abstract Induced pluripotent stem cells are powerful tools for disease modeling, drug screening, and cell transplantation therapies. These cells can be generated directly from somatic cells by ectopic expression of defined factors through a reprogramming process. However, pluripotent reprogramming is an inefficient process because of various defined and unidentified barriers. Recent studies dissecting the molecular mechanisms of reprogramming have methodically improved the quality, ease, and efficiency of reprogramming. Different strategies have been applied for enhancing reprogramming efficiency, including depletion/inhibition of barriers (p53, p21, p57, p16Ink4a /p19Arf, Mbd3, etc.), overexpression of enhancing genes (e.g., FOXH1, C/EBP alpha, UTF1, andGLIS1 ), and administration of certain cytokines and small molecules. The current review provides an in-depth overview of the cutting-edge findings regarding distinct barriers of reprogramming to pluripotency and strategies to enhance reprogramming efficiency. By incorporating the mechanistic insights from these recent findings, a combined method of inhibition of roadblocks and application of enhancing factors may yield the most reliable and effective approach in pluripotent reprogramming.